EFFECTIVE MANAGEMENT IS THE KEY TO SCHOOL IMPROVEMENT - TSUKUDU, AMELIA (My University, 2012)
A decade of democracy is marked by the change of several government organisations, including schools. The reception of change from apartheid to democracy was a challenge to most government institutions. This resulted in yet other challenges as these organisations and institutions were tried to adapt to a new way of doing things. The Gauteng Department of Education, in its endeavor to support schools that were as the results of poor performance and dysfunction, triggered programmes and projects to improve such schools. The Education Action Zone (EAZ) was established to assist such schools to do better. The services rendered to these schools through the EAZ project were aimed at equipping the principals, School Management Teams (SMTs), School Governing Bodies (SGBs) and Learner‟s Representative Councils (LRCs) to improve the quality of education. The general results of these intervention programmes were good. The improvement of Grade Twelve results in the poor performing schools was one indication that the EAZ Project and the district offices‟ effort to support school was worth it. The beneficiary schools from the abovementioned project and several other projects that were triggered to improve schools were all faced with a new set of challenges as organisations. They had to sustain the triggered improvement process and to see to it that their respective schools continually improve, even after the intervention has stopped. The onus is left on individual schools to continue this process. This research project explored the sustainanability of these interventions with the purpose to look into why schools fail to sustain improvement. The findings 6 were that school fail to sustain change, which manifest as school improvement, because lack of understanding about change and the implications that come with poor management of change. It was further found that schools do not have well developed frameworks, which consist of structures such as communication. Relationships between principals and other stakeholders in education as well as the relationship between the school and the adjacent community were noted as another reason that inhibits improvement and retards the progress towards school improvement. These findings were suggestive of the fact that principals need to resume their responsibility as managers, leaders and agents of change in order for schools to improve and to sustain the achieved improvement
MM - P&DM
Keywords: School management; Management of schools